Therapeutic Salivary Monitoring of Perampanel in Patients with Epilepsy Using a Volumetric Absorptive Microsampling Technique - Michela Palmisani; Elena Tartara; Cecilie Johannessen Landmark; Francesca Crema; Valentina De Giorgis; Costanza Varesio; Cinzia Fattore; Paola Rota; Emilio Russo; Valentina Franco (MDPI AG, 2023)
The objective of this study was to validate a novel assay using the volumetric absorptive microsampling (VAMS) technique combined with liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) for the determination of the antiseizure medication perampanel in saliva and its clinical applicability in patients with epilepsy. VAMS tips were loaded with 30 μL of saliva and dried for 60 min. Analytes were extracted with methanol. The supernatant was evaporated under a gentle stream of nitrogen and reconstituted with 60 μL of methanol. Separation and quantification were achieved on a monolithic column connected to a mass spectrometer. Calibration curves were linear between 0.5 and 300 ng/mL. Intra- and inter-day accuracy was within 85.6-103.2% and intra-day and inter-day precision did not exceed 12.1%. Perampanel was stable in samples collected by VAMS and stored under different storage conditions. The VAMS-LC-MS/MS method was validated according to internationally accepted criteria and tested in patients with epilepsy who were receiving a combination of perampanel and other antiseizure medications. The method showed adequate bioanalytical performances, holding great potential as an alternative strategy to support domiciliary TDM in patients with epilepsy treated with perampanel according to the simplicity of sample collection.